2022
DOI: 10.2196/30416
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effectiveness of a Smartphone App Combined With a Smart Band on Weight Loss, Physical Activity, and Caloric Intake in a Population With Overweight and Obesity (Evident 3 Study): Randomized Controlled Trial

Abstract: Background Multicomponent mobile health approaches can improve lifestyle intervention results, although little is known about their long-term effectiveness. Objective This study aims to evaluate the long-term effectiveness (12 months) of a multicomponent mobile health intervention—combining a smartphone app, an activity tracker wristband, and brief counseling, compared with a brief counseling group only—on weight loss and improving body composition, phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 67 publications
5
36
0
1
Order By: Relevance
“…Finally, our findings did not suggest a significant reduction in total calorie intake per day, potentially because of the small sample size. However, similar findings were reported in a large RCT that included patients with existing medical conditions [ 43 ]. The use of a smartphone app together with a smart activity band resulted in greater weight loss 12 months into the program, where both the intervention and control groups were found to have decreased their calorie intake comparably.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, our findings did not suggest a significant reduction in total calorie intake per day, potentially because of the small sample size. However, similar findings were reported in a large RCT that included patients with existing medical conditions [ 43 ]. The use of a smartphone app together with a smart activity band resulted in greater weight loss 12 months into the program, where both the intervention and control groups were found to have decreased their calorie intake comparably.…”
Section: Discussionsupporting
confidence: 86%
“…SAlBi educa results agree well with the EVIDENT II nutrition app [ 24 ], which increased the intake percentage of carbohydrates (1.1%) and decreased the intake percentage of total fats (1.0%) in the general population. Additionally, the EVIDENT 3 app also enhanced the carbohydrate intake (plus 3.8 g/day) and decreased the total fat intake (minus 4.7 g/day) in an overweight and obese population, although the app’s effect was not significant [ 51 ]. In the same sense, the Lost it!…”
Section: Discussionmentioning
confidence: 99%
“…Although physical activity of moderate or vigorous intensity increased more in the application + counselling group than in the counselling-only group, the results of the EVIDENT 2 study, conducted in the general population, found no differences when comparing the increase between the two groups [ 28 ]. Likewise, although with some change in body composition variables, the EVIDENT 3 study, conducted in an overweight or obese population, did not show relevant changes in the amount and intensity of physical activity or in nutritional habits in the group that used the app and the smartband compared to the control group [ 29 ]. Only a population of older people with type 2 diabetes mellitus obtained beneficial results in terms of increased physical activity and better adaptation to the MD [ 11 , 30 ].…”
Section: Discussionmentioning
confidence: 99%